Formulasi Formulasi dan Evaluasi Gel Ekstrak Daun Nangka (Artocarpus heterophyllus Lam.) dengan Gelling Agent CMC Na: Gel daun nangka - eryani, MIKHANIA CHRISTININGTYAS ERYANI (Jurusan Farmasi, Politeknik Kesehatan Kementerian Kesehatan Aceh, 2024)
Hand sanitizer is a preparation in the form of a gel that is widely used by the public as a practical hand washing tool. Jackfruit leaves (Artocarpus heterophyllus Lam.) have antibacterial properties that can be used for hand sanitizers. This study aims to formulate and evaluate jackfruit leaf extract gel with CMC Na gelling agent at concentrations of 1% (F1), 2% (F2) and 3% (F3). Evaluation of physical properties carried out includes organoleptic tests, homogeneity, pH, spreadability and viscosity. The results showed that all formulas were brown, smelled of mint, and homogeneous. F1 was slightly thick, F2 was thick and F3 was very thick. The pH of F1, F2 and F3 were 5.8 ± 0.05; 5.9 ± 0.05, and 5.8 ± 0.1. The spreadability of F1, F2 and F3 were 6.6 ± 0.49 cm respectively; F2 6.4±0.30 cm and F3 5.5±0.15 cm. The viscosity of F1, F2 and F3 were 13.3±2.88 dPa.s; 25±0 dPa.s and 30±0 dPa.s respectively. Based on these results, it can be concluded that the variation of CMC Na concentration affects the organoleptic shape, spreadability and viscosity but does not affect the organoleptic odor and color, homogeneity and pH